Treatment of delayed union of the forearm with extracorporeal shockwave therapy: a case report and literature review - Ryskalin, Larisa; Fulceri, Federica; Morucci, Gabriele; Dell’Agli, Stefania; Soldani, Paola; Gesi, Marco (Frontiers in Endocrinology, 2023)
Compared to other long bones, forearm fractures are particularly challenging due to the high rate of complications. These include malunion, delayed/nonunion, wrist and elbow movement reduction, and pain. Surgical procedure is considered the gold standard for managing delayed union and nonunion of the long bones. However, in the last decades, extracorporeal shockwave therapy (ESWT) has emerged as an effective and less invasive approach to enhance bone regeneration and fracture healing, avoiding major complications of surgical procedures. In contrast to the broad literature reporting good clinical results of ESWT in the treatment of nonunions, there is currently limited evidence regarding the clinical application of shock waves on long bone delayed fractures, particularly those of the forearm. In the present paper, we report a case of delayed bone healing of the diaphyseal region of the ulna treated with focused ESWT. The successful case experienced bone healing at the fracture site in less than 3 months after initial ESWT treatment. Acknowledging the limitation of reporting a case report, however, the remarkable clinical results and the absence of side effects contribute valuable information in support of the use of ESWT as an effective alternative to standard surgery for forearm fractures.